2015
DOI: 10.1016/j.cellsig.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Mu opioid receptor stimulation activates c-Jun N-terminal kinase 2 by distinct arrestin-dependent and independent mechanisms

Abstract: G protein-coupled receptor desensitization is typically mediated by receptor phosphorylation by G protein receptor kinase (GRK) and subsequent arrestin binding; morphine, however, was previously found to activate a c-Jun N-Terminal Kinase (JNK)-dependent, GRK/arrestin-independent pathway to produce mu opioid receptor (MOR) inactivation in spinally-mediated, acute anti-nociceptive responses Melief, et. al., 2010 [1]. In the current study, we determined that JNK2 was also required for centrally-mediated analgesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Our results suggest that JNK3 plays the least prominent role in morphine tolerance. These findings are novel in showing that all three forms of JNK contribute to morphine tolerance, and they are consistent with previous work demonstrating that JNK2 can mediate tolerance to morphine [11, 18]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results suggest that JNK3 plays the least prominent role in morphine tolerance. These findings are novel in showing that all three forms of JNK contribute to morphine tolerance, and they are consistent with previous work demonstrating that JNK2 can mediate tolerance to morphine [11, 18]. …”
Section: Discussionsupporting
confidence: 91%
“…Morphine results in an increase in spinal JNK phosphorylation through a protein kinase C (PKC)-dependent process [11]. Furthermore, this effect was abolished in JNK2 KO, but not JNK1 KO or JNK3 KO mice [18]. Both of these studies also demonstrated that JNK2 KO mice have a reduction in acute morphine tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative strategy is to use mouse embryo fibroblasts derived from arrestin-null animals (79), but these cells are challenging to transfect, limiting their usefulness. This has meant that despite the caveats described above and the fact that such arrestin-null mouse embryo fibroblasts have shown that, in this cell type, activation of the extracellular signal-regulated kinases ERK1/2 by certain ligands at the β 2 -adrenoreceptor requires an arrestin (10), much of the basis of underpinning analysis of arrestin signaling has derived from studies in more tractable, transformed cell lines, including human embryonic kidney (HEK) 293 cells where arrestin levels have been reduced but not completely eliminated (1114). …”
Section: Introductionmentioning
confidence: 99%